2007
DOI: 10.1677/jme.1.02110
|View full text |Cite
|
Sign up to set email alerts
|

The MN1 oncoprotein activates transcription of the IGFBP5 promoter through a CACCC-rich consensus sequence

Abstract: The IGF-binding protein (IGFBP) family consists of six proteins that are expressed and secreted in different tissues. The proteins are regulators of physiological processes throughout the body by modulating the activity of IGF-I and IGF-II. In this article, we describe the coordinated expression of IGFBP5 and MN1 in meningiomas. MN1 is a transcriptional co-activator and we show that MN1 stimulates the IGFBP5 promoter in Hep3B cells. A CACCC-containing sequence, located 140 bp upstream of the transcription star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…This protein binding to the Ϫ253/ Ϫ242 probe appeared only after OA treatment and remained after TCPOBOP and OA co-treatment. Based on the nucleotide sequence CACCCACACA, various transcription factors, such as SP1, AP1, Kruppel-like factors, and EGR1, were selected (16,17) and tested for their binding to the Ϫ253/Ϫ242 probe; only the EGR1 antibody supershifted the specific band (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
“…This protein binding to the Ϫ253/ Ϫ242 probe appeared only after OA treatment and remained after TCPOBOP and OA co-treatment. Based on the nucleotide sequence CACCCACACA, various transcription factors, such as SP1, AP1, Kruppel-like factors, and EGR1, were selected (16,17) and tested for their binding to the Ϫ253/Ϫ242 probe; only the EGR1 antibody supershifted the specific band (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
“…were correlated to a poor prognosis in patients with AML, and MN1 overexpression induced myeloid malignancy in mice (Heuser et al, 2007;Meester-Smoor et al, 2007). Therefore, MN1 expression in AMU-AML1 cells might play a role in the disease progression and possibly in leukemogenesis.…”
Section: Establishment Of a Cell Line Carrying T(12;22)mentioning
confidence: 99%
“…Many genes have been reported as fusion partners for TEL; these fusion partners include AML1, PDGFbR, MN1, ABL, MDS1/EVI1, JAK2, and others (Bohlander, 2005). The MN1 gene is located on chromosomal band 22p11, and the product of MN1 is associated with leukemogenesis as a coactivator of transcription (van Wely et al, 2003;Heuser et al, 2007;Meester-Smoor et al, 2007). A high level of MN1 mRNA expression is predictive of a poor outcome in patients with acute myeloid leukemia (AML) with normal karyotype (Heuser et al, 2006;Langer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…24 We also found that the IGFBP5 gene (whose promoter transcription can be activated by the MN1 gene product) was significantly suppressed (Table S1). 31 Interestingly, MN1 can both stimulate and inhibit transcription of this gene. Overexpression of MN1 was also reported in the development of acute myeloid leukemia.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…IGFBP5 is also upregulated by MN1 and linked to other cancer types, including glioblastoma multiforme. 31,49 We further identified a core region within the oncogenic coexpression module, consisting of the hub genes GAB2 and KLF2. The additional hub genes ID1 and CTF1 were directly connected to these members of the core region.…”
Section: 40mentioning
confidence: 99%